MATHEMATICAL TECHNIQUES IN HIGHWAY CONSTRUCTION: IMPORTANCE AND IMPLEMENTATION - Kaur, Daljeet; Kumar, Raj (International Journal of Psychosocial Rehabilitation, 2021)
The importance of planning and structuring in development projects is generally obvious during the execution of individual exercises; however, the suggestions that frequently emerge from poorly controlled exercises frequently result in overspending, delays, unsatisfactory items, or complete project disappointment. During the execution and control of development activities, there is a need for a comprehensive strategy; this is especially true when the project is seen as being muddled by a variety of objectives. It is assumed that using project planning and structure using mathematical methodologies will improve the organisation of issues affecting project parameters such as cost, time, quality, and extension. The concept is applied to the investigation of a real project, which includes the creation of holding dividers to validate key planning steps and the coordination of parameters using mathematical techniques to characterise the project baseline plan: inferential insights in quality confirmation, straight programming in the work breakdown structure, and choice hypothesis in the work breakdown structure systems administration/booking.